Cover Picture: Macromol. Mater. Eng. 10/2014. Issue 10 (October 2014) - Dong, Jie; Yin, Chaoqing; Zhang, Zixin; Wang, Xinyu; Li, Haibei; Zhang, Qinghua
<x xml:space="preserve">Abstract</x> Cover: Co‐polyimide fibers are prepared successfully. The introduction of benzimidazole units in the polymer chains enhances the hydrogen‐bonding intermolecular interaction and increases the regularity of the molecule packing. Therefore, the fibers exhibit excellent mechanical properties and outstanding thermal stabilities. Further details can be found in the article by J. Dong, C. Yin, Z. Zhang, X. Wang, H. Li, Q. Zhang* on page 1170. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>